Sixteen new lung function signals identified through 1000 Genomes Project reference panel imputation - Artigas, María Soler; Wain, Louise V.; Miller, Suzanne; Kheirallah, Abdul Kader; Huffman, Jennifer E.; Ntalla, Ioanna; Shrine, Nick; Obeidat, Ma’en; Trochet, Holly; McArdle, Wendy L.; Alves, Alexessander Couto; Hui, Jennie; et al. (Nature Publishing Group, 2015)
Lung function measures are used in the diagnosis of chronic obstructive pulmonary disease. In 38,199 European ancestry individuals, we studied genome-wide association of forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC) and FEV1/FVC with 1000 Genomes Project (phase 1)-imputed genotypes and followed up top associations in 54,550 Europeans. We identify 14 novel loci (P<5 × 10−8) in or near ENSA, RNU5F-1, KCNS3, AK097794, ASTN2, LHX3, CCDC91, TBX3, TRIP11, RIN3, TEKT5, LTBP4, MN1 and AP1S2, and two novel signals at known loci NPNT and GPR126, providing a basis for new understanding of the genetic determinants of these traits and pulmonary diseases in which they are altered.